2002
DOI: 10.1007/s00210-001-0515-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in α 1 -adrenergic vascular reactivity in monocrotaline-treated rats

Abstract: In rats, injection of monocrotaline (MCT) causes pulmonary hypertension that leads to right ventricular failure. The aim of the present study was to characterize the responses of various vessels (the pulmonary artery, the thoracic aorta and small mesenteric arteries) to noradrenaline (NA; 10(-10)-10(-5) M) and carbachol (10 microM) in MCT-treated rats. For this purpose 6-week-old male Wistar rats ( n=13) were treated with 60 mg/kg MCT i.p. After 4-6 weeks the rats were killed and the heart, lungs and vessels r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
1
6
0
1
Order By: Relevance
“…Because we had to use in the present study a new Wistar rat strain, we performed preliminary dose-finding experiments that revealed that 50 mg/kg body weight sc was an appropriate dose of MCT for this rat-strain with regard to survival and induction of right heart hypertrophy due to pulmonary hypertension and with regard to similarity to our previous studies, where we had used another rat strain and induced right heart hypertrophy with a single intraperitoneal (IP) injection of 60 mg MCT/kg body weight. 8,10,14 However, analogous to our previous studies, MCT-treated animals show, in general, significantly less weight gain than control animals; therefore, the MCT-treated rats had free supply to food, whereas control rats were restricted to the quantity of food consumed by the MCT-treated rats the previous day. 10,14 -15 All animals had free access to water.…”
Section: Animalssupporting
confidence: 81%
See 1 more Smart Citation
“…Because we had to use in the present study a new Wistar rat strain, we performed preliminary dose-finding experiments that revealed that 50 mg/kg body weight sc was an appropriate dose of MCT for this rat-strain with regard to survival and induction of right heart hypertrophy due to pulmonary hypertension and with regard to similarity to our previous studies, where we had used another rat strain and induced right heart hypertrophy with a single intraperitoneal (IP) injection of 60 mg MCT/kg body weight. 8,10,14 However, analogous to our previous studies, MCT-treated animals show, in general, significantly less weight gain than control animals; therefore, the MCT-treated rats had free supply to food, whereas control rats were restricted to the quantity of food consumed by the MCT-treated rats the previous day. 10,14 -15 All animals had free access to water.…”
Section: Animalssupporting
confidence: 81%
“…11 Data from the literature and our own data show that a single injection of the pyrrolizidine alkaloid monocrotaline induces in rats within 14 days after application severe pulmonary hypertension, resulting first in development of right ventricular hypertrophy due to apparent pressure overload and then in right heart insufficiency accompanied by an increase in sympathetic nervous system activity. [7][8]10,[12][13][14] Thus, the monocrotaline rat model allows to investigate whether pressure overload evoked hypertrophy per se can induce the characteristic alterations in the cardiac ␤-adrenoceptor system seen in chronic heart failure, or whether those changes can only occur when hypertrophy is accompanied by neurohumoral activation. In order to study this, we assessed in monocrotaline-treated rats, ␤-adrenoceptor density and subtype distribution, G proteincoupled receptor kinase activity, neuronal noradrenaline transporter density and activity and plasma noradrenaline levels at two time-points after monocrotaline-treatment: one group (within 13 to 19 days after application) that had developed right ventricular hypertrophy but did not show signs of neurohumoral activation (no increase in plasma noradrenaline) and one group (within 21 to 28 days after application) that showed right ventricular hypertrophy and increased plasma noradrenaline levels (as index of neurohumoral activation).…”
mentioning
confidence: 99%
“…E1 after 3 weeks from injection of MCT, sildenafil (50 mg kg -1 ) and everolimus (1 mg kg -1 ) were administered rats orally for 21 days; SLD ? E3 after 3 weeks from injection of MCT, sildenafil (50 mg kg -1 ) and everolimus (3 mg kg -1 ) were administered rats orally for 21 days PH, it was observed that endothelium-dependent relaxation responses were significantly decreased compared to those in the control group owing to decreases in the production of NO secondarily to endothelial damage [15,16,26,34]. Ach relaxation responses in the treated groups, particularly the SLD ?…”
Section: Discussionmentioning
confidence: 94%
“…It causes pulmonary artery neomuscularisation, hyperplasia and hypertrophy of smooth muscle cells, inflammation, and endothelial damage as well as the obliteration of pulmonary vasculature and resultant right ventricular hypertrophy and failure [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the contractile activity of the pulmonary artery in MCT-treated rats have also been demonstrated by several research groups; however, the data from the studies have been conflicting. While several studies have found attenuated constrictive responses to vasoconstrictors such as norepinephrine and 5-hydroxytryptamine in isolated pulmonary arteries from MCTtreated rats [5,25,38], others have demonstrated increased responsiveness [3,14,17,22,40]. It has also been reported that the main pulmonary artery from MCT-treated rats is depolarized [15,39], which is not attributable to the endothelial damage [15], and that the endothelial-denuded pulmonary artery from MCT-treated rats has active basal tone in the resting state [15,34].…”
Section: Introductionmentioning
confidence: 97%